Musical Heritage and Cultural Identity: Interpreting the Symbolic Meaning of Silotuang in Dayak Bidayuh Life - Ramadhan, Iwan; Sagala, Mastri Dihita; Putra, Zakarias Aria Widyatama; Olendo, Yudhistira Oscar; Dewantara, Jagad Aditya; Hardiansyah, Muhammad Agus (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2025)
This study aims to preserve and maintain the traditions and local wisdom values of the Dayak Bidayuh community in Jagoi Village through investigations conducted to enhance understanding of Indonesia's rich cultural diversity. This research addresses the lack of appreciation for the traditional musical instrument Silotuang, especially among the younger generation. In the face of rapid globalization, many traditions are at risk of extinction, making it crucial to document and analyze the values in the "Mighty of Silotuang" music performance, as well as its reflection in daily practices. Using an ethnographic approach, this research involves direct observation, particularly during the preparation process until the conclusion of the Silotuang music performance. In-depth interviews were conducted with community leaders, traditional musicians, and the local community around Jagoi Babang. The data collected, documented, and analyzed to reveal how local wisdom is embedded in rituals, symbols of traditional music, and daily practices. These findings aim to provide a comprehensive understanding of the Silotuang musical instrument and offer recommendations for maintenance traditional music in social cultural aspects. This study concludes that preserving local wisdom strengthens cultural identity and pride within the Dayak Bidayuh community in the Jagoi Babang. These findings highlight the importance of the contribution of the younger generation in understanding and appreciating living cultural heritage to address the urgency of intangible cultural heritage conservation.